Reestruturação produtiva na indústria brasileira: evolução e seus principais impactos - Martins, Luiz Claudio do Monte (2006)
This thesis evaluates the process of productive reorganization into Brazilian industrial sector and analyzes the influence of conjunctural and structural economic factors on the same, as well as the main results of such process in terms of technological innovation, productivity, added value and job. Taking the academic literature, the first chapter presents the structural changes through which have the industrial sector has passed in the world since the mid-seventies decade, the transformations of the productive paradigm and the origins of reorganization in Brazil. The second chapter portrays the evolution of Brazilian economy in 1990 s, revealing liberal politicals that were implanted in this time and their consequence on industrial sector. The third chapter tends to show the analysis on the evolution of industrial reorganization in Brazil, putting emphasis on behavior examination of technological innovation, productivity, value and job generation. Lastly, the main conclusions of this study are presented